Halal Authentication of Gelatin Capsules using Polymerase Chain Reaction, Fourier Transform Infrared Spectroscopy and Chemometric Methods - Ahlam Inayatullah (Universiti Sains Islam Malaysia, 2024)
Gelatin, a high molecular weight polypeptide obtained from protein, is an important material for capsules of health supplements.A reliable method for halal authentication of gelatin is needed because some supplement products are capsulated using gelatinfrom non-halal source.In this study a real-time polymerase chain reaction (PCR) assay using SYBR green fluorescent dye was done to detect porcine in gelatin capsules supplements. The method combined the porcine and bovine specific primers and SYBR green dye to specifically amplify a 120-bp fragment of bovine and 131-bp fragment of porcine mitochondrial Cytochrome b (CYT b) gene.Mitochondrial genes were present in multiple copies and thus ensure available targets even in degraded samples. Using basic local alignment search tools (BLAST) with 1 ng DNA standard, bovine and porcine species yielded a melt temperature at ±80.00 °C only with one specific peak in the melt curve reaction, demonstrating the porcine and bovine specificity of the primers. A sensitivity test with 5-fold serial dilution revealed that the assay can determine 10¯¹ nġ/ų1 of porcine and bovine DNA with efficiencies of 97.4% and 90.6% with good repeatabilities and high correlation coefficients (R²= 0.995 bovine; R²= 0.962 porcine).From a total of 20 samples of supplements in capsules with halal certifications from various countries,eight (8) samples were confirmed with adulteration of porcine DNA while four samples were confirmed to contain bovine DNA.FTIR technique was then used to confirm the results of real-time PCR in terms of chemical representation. The FTIR results were later confirmed using principal component analysis (PCA).Eight wavelengths chosen from the twelve samples were 694,1249,1342,1404,1450,1558,1635 and 3271 cm¯¹.